Global networks: issues and tactics in the Bakun Dam Project - Kartini Aboo Talib Khalid (Penerbit UKM, 2007)
The role of global networks is increasingly important in influencing state’s decision on grand project. Tactics and strategies are employed across borders to build up cases and arguments to influence state’s decision. Global actors such as the non-governmental organizations particularly environmentalist groups adopt strategies that bypass their state and search out for international allies to bring pressure on their state from outside. Sahabat Alam Sekitar (SAM) and other international allies who are members of World Commission on Dam (WCD) rally campaigns for the severe environmental and social structure effect on the Bakun dam project. Global networks presented their findings on eight large dams that have put pressure on the Asea Brown Boveri (ABB) and the Malaysian government to reconsider the big-dam project. Here the discussions on tactics and strategies by global networks are vital because a similar analysis can be applied in examining the impact of global networks on state’s decision. However, actions from global networks have to be consistent and continuous to convince state actors. Local networks have to find ways to redefine issues concerning environments and people who are affected as a way to maintain endorsement from international networks. If supports are not consistent and continuous, the impact of collective efforts from global networks is rather subtle or perhaps forgettable.